Novel Thiosemicarbazone Derivatives from Furan-2-Carbaldehyde: Synthesis, Characterization, Crystal Structures, and Antibacterial, Antifungal, Antioxidant, and Antitumor Activities - Wilfredo Hernández; Fernando Carrasco; Abraham Vaisberg; Evgenia Spodine; Maik Icker; Harald Krautscheid; Lothar Beyer; Carmen Tamariz-Angeles; Percy Olivera-Gonzales (Journal of Chemistry)
Ten new thiosemicarbazone derivatives, furan-2-carbaldehyde thiosemicarbazone (1), 3-methyl-furan-2-carbaldehyde thiosemicarbazone (2), 5-hydroxymethyl-furan-2-carbaldehyde thiosemicarbazone (3), 5-trifluoromethyl-furan-2-carbaldehyde thiosemicarbazone (4), 5-nitro-furan-2-carbaldehyde thiosemicarbazone (5), 5-phenyl-furan-2-carbaldehyde thiosemicarbazone (6), 5-(2-fluorophenyl)-furan-2-carbaldehyde thiosemicarbazone (7), 5-(4-methoxyphenyl)-furan-2-carbaldehyde thiosemicarbazone (8), 5-(1-naphthyl)-furan-2-carbaldehyde thiosemicarbazone (9), and 5-(1H-Pyrazol-5-yl)-furan-2-carbaldehyde thiosemicarbazone (10) were synthesized by condensing thiosemicarbazide with the respective furan-2-carbaldehyde in methanol. The prepared compounds were characterized by spectroscopic studies (FT-IR and NMR) and electrospray mass spectrometry. The molecular structures of 2, 6, 7, and 8 have also been determined by X-ray crystallography. Compounds 2, 6, and 7 crystallize in the E conformation about the N1-C6, N1-C11, and N1-C11 bonds, respectively, while 8 adopts the Z conformation about the N1-C12 bond with the presence of an intramolecular N2-H…O2 hydrogen bond. All prepared thiosemicarbazone derivatives were evaluated for their in vitro antibacterial, antifungal, and antitumor activities against Staphylococcus aureus strains, Candida albicans/Candida tropicalis fungi, and seven human tumor cell lines (HuTu80, H460, DU145, M-14, HT-29, MCF-7, and LNCaP), respectively. The antioxidant activity was also studied by the DPPH assay. Compound 5 exhibited significant antibacterial activity against Staphylococcus aureus ATCC700699 (MIC = 1 μg/mL) compared to the nitrofurantoin and gentamicin reference drugs (MIC = 1–25 and 10->100 μg/mL, respectively). Compound 4 was ten times less active than amphotericin B (MIC = 5 μg/mL) against Candida albicans (ATCC90028 and ATCC10231), while 1 exhibited a moderate effect of scavenging of DPPH radical (IC50 = 40.9 μg/mL) in comparison to ascorbic acid reference compound (IC50 = 22.0 μg/mL). Among all the studied thiosemicarbazones, 5 showed a higher cytotoxic activity (IC50 = 13.36–27.73 μΜ) in relation to the other tested compounds (IC50 = 34.84—>372.34 μΜ) against all tested cell lines, except the LNCaP cell line, exhibiting its highest antiproliferative activity (IC50 = 13.36 μΜ) on the HuTu80 cell line. Besides, 8 and 9 exhibited high antitumor activity (IC50 = 13.31 and 7.69 μΜ, respectively) against the LNCaP cells.